QoS Issues in Complex-Based High Altitude Platform Communication Systems - Birkos, Konstantinos; Chrysikos, Theofilos; Kotsopoulos, Stavros (Communications - Scientific letters of the University of Zilina, 2007)
The use of High Altitude Platforms is a promising solution towards the integration of different wireless networks. Complex-based High Altitude Platform communication systems can offer high quality wireless services combined with enhanced bandwidth efficiency. Inter-system handover and power control are major factors affecting the provided quality of service. The impact of these factors under strong fading environments is studied in the present work.